Alcohol induced hepatic retinoid depletion is associated with the induction of multiple retinoid catabolizing cytochrome P450 enzymes - Ferdouse, Afroza; Agrawal, Rishi R.; Gao, Madeleine A.; Jiang, Hongfeng; Blaner, William S.; Clugston, Robin D. (PLOS ONE, 2022)
Chronic alcohol consumption leads to a spectrum of liver disease that is associated with significant global mortality and morbidity. Alcohol is known to deplete hepatic vitamin A content, which has been linked to the pathogenesis of alcoholic liver disease. It has been suggested that induction of Cytochrome P450 2E1 (CYP2E1) contributes to alcohol-induced hepatic vitamin A depletion, but the possible contributions of other retinoid-catabolizing CYPs have not been well studied. The main objective of this study was to better understand alcohol-induced hepatic vitamin A depletion and test the hypothesis that alcohol-induced depletion of hepatic vitamin A is due to CYP-mediated oxidative catabolism. This hypothesis was tested in a mouse model of chronic alcohol consumption, including wild type and Cyp2e1 -/- mice. Our results show that chronic alcohol consumption is associated with decreased levels of hepatic retinol, retinyl esters, and retinoic acid. Moreover, the depletion of hepatic retinoid is associated with the induction of multiple retinoid catabolizing CYPs, including CYP26A1, and CYP26B1 in alcohol fed wild type mice. In Cyp2e1 -/- mice, alcohol-induced retinol decline is blunted but retinyl esters undergo a change in their acyl composition and decline upon alcohol exposure like WT mice. In conclusion, the alcohol induced decline in hepatic vitamin A content is associated with increased expression of multiple retinoid-catabolizing CYPs, including the retinoic acid specific hydroxylases CYP26A1 and CYP26B1.